Overriding the rules of international tax treaties by the means of the national law of one of the parties (“Tax treaty override”) - I. A. Khavanova (Правоприменение, 2023)
Subject of research. The article is dedicated to the “tax treaty override”; it outlines debatable aspects, associated herewith. “Tax treaty override” is an action (in certain cases - omission of action) to expand taxation beyond (jurisdictional boundaries), defined in double taxation agreements which is implemented mainly through the intentional alteration of national legis-lation. The correlation between national and international legal norms has major impact upon the agreements on double taxation of income taking into account that many states including Russia are participants to the Multilateral Convention to Implement Tax Treaty Related Measures to Prevent Base Erosion and Profit Shifting 2016, which modifies rules of the men-tioned agreements and therefore begets a large number of possible collisions.Goal of the article. The goal of the article is to demonstrate that even if constitutional pro-visions don’t prevent the adoption of legislation on taxes and charges in contradiction with international obligations – that doesn’t imply that the latter lack legal significance. The goal also includes revealing specific features of double taxation agreements one of which is deep integration with domestic tax legislation that doesn’t stand still, but is evolving constantly. Methods of research. The preparation phase included the following research methods: formallogical analysis, system-based analysis, description, juxtaposition, synthesis and summarizing.Basic outcomes. The author draws a conclusion that the alteration (expansion) of tax jurisdiction which impacts i.a. the contents of tax residents’ rights of one or both treaty countries (party countries, treaty states) is actually the essence of tax treaty override. The main objectives of regulatory impact are jurisdictional capabilities (distributive rules) of states and tax reliefs for residents (individuals for the tax agreements). The phenomenon under consideration represents an artificially generated collision between the provisions of tax treaties and more recent norms of domestic legislation of one of the countries subject to a tax agreement, while the mentioned issue should be resolved in favor of domestic regulations. The main goals of regulatory impact include: jurisdictional capabilities of states (dis-tributive rules) and tax reliefs or benefits for residents (individuals for the tax agreements). Tax treaty override emerges when a provision of a law prevails and cannot be overridden by the means of tax agreements, including the test of correspondence between a national legal definition and the agreement context. At the same time legal changes that have prevailing power may correspond with international law (reasonable protection of national tax base) since the treaty states seek to eliminate double taxation without creating possibility of taxation freedom or reduction of taxation through tax avoidance and tax evasion.